FORMULATING STRATEGIES BASED ON LOCAL COMMUNITY’S PERCEPTIONS FOR CAVE AND BAT ECOTOURISM DEVELOPMENT: A CASE STUDY OF TOGENRA CAVE IN BARRU, SOUTH SULAWESI - Risma Illa Maulany; Ahmad Syarif Ansharullah; Andi Siady Hamzah; Nasri Nasri (Indonesian Journal of Forestry Research, 2023)
Togenra cave in Madello Village, Barru Regency (South Sulawesi) is located in the Tonasa Karst Formation, known as one of the largest formations in Asia and is also popular for its unique features and functions. Currently, the local government has not yet established a regulation on the management of the cave, and locals are free to access the cave for calcium and guano mining which can threaten the ecosystem of the cave. Therefore, it is necessary to develop non-consumptive use of the cave, through ecotourism that can provide long-term benefits to the local communities. This study aimed to 1) examine the community’s perceptions toward the cave, bats and conservation; 2) formulate strategies by assessing the potency of the cave and bat species as an ecotourism spot based on the local’s perceptions; and 3) provide recommendations for the local government in supporting both ecotourism and conservation in the area. The study was conducted from August 2020 to February 2021. A set of questionnaires were to 31 respondents living within a radius of 1 km from Togenra cave. Formulation of strategies were done by using combined analyses of Strength, Weakness, Opportunity, Threats (SWOT) and  Analysis of Hierarchy Process (AHP). Our analyses indicate a growth strategy trend (Quadrant I). Several strategies drawn emphasize on improving local’s knowledge and perceptions, active involvement of locals, establishment of local management initiatives and regulations, capacity enhancement, and implementation of a stakeholders’ forum. These findings can become a baseline in planning and developing both bat-cave tourism as well as conservation efforts in the area